Ces filles accusées et repérées par le travail social - Jean-François Laé (Astérion)
Browsing through his work from 1975 to 2010, Jean-François Laé discovers the very powerful presence of a figure, “the teenage mother”, who is caught up in the nets of the courts, social work and institutional supervision. He traces the sinuous path of his research and of his own biography, in order to re-examine a connection from the 1950s, civil case law from the end of the 19th to the beginning of the 20th century, police archives from the 1960s, and the archives of social institutions.